A Qualitative Study: Mothers' Experiences of Their Child's Late-Onset Pompe Disease Diagnosis Following Newborn Screening - Kaylee Crossen; Lisa Berry; Melanie F. Myers; Nancy Leslie; Cecilia Goueli (MDPI AG, 2022)
Pompe disease was added to the United States recommended uniform screening panel in 2015 to avoid diagnostic delay and implement prompt treatment, specifically for those with infantile-onset Pompe disease (IOPD). However, most newborns with abnormal newborn screening (NBS) for Pompe disease have late-onset Pompe disease (LOPD). An early diagnosis of LOPD raises the question of when symptoms will arise which is challenging for parents, patients, and providers managing an LOPD diagnosis. This study aimed to characterize mothers' experiences of their child's LOPD diagnosis and medical monitoring. A qualitative descriptive approach was chosen to gain an in-depth understanding of parental experiences. Eight mothers were interviewed about their experiences with positive NBS and diagnosis, experiences with living with the diagnosis, and experiences with medical monitoring. Interview transcripts were analyzed through conventional content analysis. Negative emotions like fear were more frequent with communication of NBS results. Participants expressed uncertainty surrounding age of symptom onset and the future. The medical monitoring experience increased worry but participants expressed that being vigilant with management reassured them. Parental emotions shifted to thankfulness and reassurance with time and education. These findings can provide guidance to providers about the psychosocial implications of receiving positive NBS results and an LOPD diagnosis.